2021
DOI: 10.1021/acsaem.1c00638
|View full text |Cite
|
Sign up to set email alerts
|

3R-MoS2 in Review: History, Status, and Outlook

Abstract: Transition metal dichalcogenides (TMDs) of molybdenum and tungsten are layered van der Waals materials that exhibit a rich array of polytypes. The different possible arrangements of the constituents of the “two-dimensional” MX2 sheets (where M = group 4–10 elements, X = chalcogen) give rise to a host of interesting and tunable phenomena. Molybdenite, or molybdenum disulfide (MoS2) in its most abundant and thermodynamically stable form, 2H-MoS2, is perhaps the most widely used TMD, though the potential applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 161 publications
0
38
0
Order By: Relevance
“…Many publications are devoted to the influence of impurities, in particular, rhenium, on the appearance of the 3 R polytype of molybdenite (Khurshudyan et al , 1969; Newberry, 1979a, 1979b; McCandless et al , 1993; Strachan et al , 2021). As a rule, molybdenite-3 R are enriched in rhenium, but сonsideration of the available analyses shows that high-rhenium natural molybdenites (up to 4.7 wt.%, Voudoris et al , 2009) can crystallise in the 2 H polytype (Newberry, 1979b; Voudouris et al 2009, Ciobanu et al , 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many publications are devoted to the influence of impurities, in particular, rhenium, on the appearance of the 3 R polytype of molybdenite (Khurshudyan et al , 1969; Newberry, 1979a, 1979b; McCandless et al , 1993; Strachan et al , 2021). As a rule, molybdenite-3 R are enriched in rhenium, but сonsideration of the available analyses shows that high-rhenium natural molybdenites (up to 4.7 wt.%, Voudoris et al , 2009) can crystallise in the 2 H polytype (Newberry, 1979b; Voudouris et al 2009, Ciobanu et al , 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Tube, bulbous and fullerene-like nanostructures are known for many synthetic 2D-materials such as elemental carbon and Mo, Re and W disulfides, etc. They draw attention due to their outstanding structure-dependent properties such as immense specific surface, outstanding electrical and catalytic properties and the possibility of their application as lubricants (Ramakrishna et al , 2010; Spear et al , 2015; Strachan et al , 2021 and references therein). Molybdenite has a layered structure formed by two-dimensional (2D) continuous layers consisting of trigonal prisms of MoS 2 with a molybdenum atom in the centre and six sulfur atoms at the top and bottom.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] In previous reports, the applications of TMDs included solid lubricants, 26 electrocatalysts, 27 photocatalysts, 28 gas sensors, 29 optoelectronics, 30,31 and rechargeable batteries. [32][33][34] As one important type of TMDs, MoS 2 has demonstrated a high mobility of 200 cm 2 V −1 s −1 and direct bandgap of 1.9 eV in the nanoscale. 35 In the review of the crystallographic configuration, MoS 2 demonstrated different phases, including the most thermodynamically stable hexagonal (2H), metastable trigonal (1T), and second most stable rhombohedral (3R) phases.…”
Section: Introductionmentioning
confidence: 99%
“…The 2H phase has a trigonal prismatic configuration, whereas 1T MoS 2 is an octahedral structure . There is also a 3R phase that has the same trigonal prismatic configuration as 2H but a different stacking order of S–Mo–S chevrons . The different crystalline phase structure leads to different and unique electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…31 There is also a 3R phase that has the same trigonal prismatic configuration as 2H but a different stacking order of S−Mo−S chevrons. 32 The different crystalline phase structure leads to different and unique electrical properties. 2H-MoS 2 , as the most thermodynamically stable phase, behaves as a n-type semiconductor with an indirect band gap of 1.2 eV (bulk) to a direct band gap of 1.8 eV (monolayer) and a charge carrier mobility of 0.1−10 cm 2 V −1 s −1 for a single layer.…”
Section: ■ Introductionmentioning
confidence: 99%